2003
DOI: 10.1523/jneurosci.23-03-00732.2003
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Functional Inhibitory Neurons in the Adult Rat Hippocampus

Abstract: Several thousand new neurons are produced each day in the adult mammalian hippocampus, among which only excitatory granule cells (GCs) have thus far been identified. In the present study, we used mutant Semliki Forest Virus vectors to express enhanced green fluorescent protein in the hippocampus, and observed that ϳ14% of newly generated neurons in the dentate gyrus of adult rats are GABAergic basket cells (BCs). With the use of double whole-cell patch-clamp recordings from BC-GC pairs in hippocampal slices, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 25 publications
4
91
1
2
Order By: Relevance
“…Activity improves the survival rate of new DG neurons (Deisseroth et al, 2004). Also, fate determination of NPCs (glia vs neurons) is activity-dependent (Liu et al, 2003). Death by suicide was unrelated to antidepressant treatment or GN number as untreated and treated MDDs had a similar percentage of suicides.…”
Section: Treatment Effect On Granule Neuron Numbermentioning
confidence: 99%
“…Activity improves the survival rate of new DG neurons (Deisseroth et al, 2004). Also, fate determination of NPCs (glia vs neurons) is activity-dependent (Liu et al, 2003). Death by suicide was unrelated to antidepressant treatment or GN number as untreated and treated MDDs had a similar percentage of suicides.…”
Section: Treatment Effect On Granule Neuron Numbermentioning
confidence: 99%
“…3 I, J ). Notably, from the cellular morphology of the YFP cells within the granule zone (Cameron and McKay, 2001;van Praag et al, 2002;Liu et al, 2003), no GABAergic neurons appear to arise from Ascl1 cells in adult dentate gyrus. Together, these results demonstrate that the Ascl1 cells detected in this paradigm are mostly type2a progenitor cells that mature into granule cell neurons by 30 d, with a subset marking a stem cell population of limited renewal potential.…”
Section: Characterization Of Ascl1 In the Adult Brainmentioning
confidence: 99%
“…This information is particularly important considering that a small subpopulation of DGCs can release GABA (53), and it would be tempting to speculate that those GABAergic DGCs might originate during adulthood. Liu and collaborators (16) have recently demonstrated that the adult DG can generate not only functional DGCs but also GABAergic interneurons. Applying a combination of viral expression of GFP and bromodeoxyuridine (BrdU) labeling, they carried out whole cell recordings from 169 pairs of cells in the DG and found 16 interneurons (probably Basket cells) that released GABA onto DGCs and were labeled with BrdU.…”
Section: Functional Neurogenesis In Tissue Culturementioning
confidence: 99%
“…The SGZ and SVZ give rise primarily to dentate granule cells (DGCs; FIGURE 1) and interneurons of the OB, respectively (1,10). Growing evidence indicates that new neurons become functionally integrated in the existing circuits (2,4,16,39,52), although the true physiological relevance of adult neurogenesis remains unknown.…”
mentioning
confidence: 99%